Edukasi Deteksi Dini Stroke Dengan Metode FAST (Face, Arm, Speech, Time) Di Kelurahan Simatorkis Sisoma Kabupaten Tapanuli Selatan - Nanda Masraini Daulay; Nefonavratilova Ritonga (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
Rapid, precise and accurate identification and detection of strokes that occur outside the hospital, whether carried out by the patient or the patient's family, has a positive effect on the success of therapy and treatment programs. This educational activity aims to increase public knowledge about early detection of stroke with the FAST method in Simatorkis Sisoma Village, South Tapanuli Regency. The activities carried out consisted of measuring blood pressure, blood sugar and cholesterol levels, distributing knowledge questionnaires, followed by education. The number of participants is 30 people who are at high risk of stroke. The results of this activity found 24 people (80%) of the community with good knowledge category. Meanwhile, 6 people (20%) are in the category of less knowledge. This activity can be continued with more specific material related to swallowing disorders in stroke patients.